A mixed valence state Mo-based metal–organic framework from photoactivation as a surface-enhanced Raman scattering substrate. (3rd March 2021) - Chen, Zhengyi; Su, Linjing; Ma, Xionghui; Duan, Zhenhua; Xiong, Yuhao
Abstract : In this work, a facile method for a mixed valence state Mo-base metal-organic framework from photo activation (UV Mo-MOF) was proposed and employed as a SERS substrates with molecule enrichment property. Abstract : As a powerful analytical tool, the surface-enhanced Raman scattering (SERS) technique is widely used to identify and quantitatively detect molecular species and usually requires a noble metal or semiconductor substrate. To expand the range of substrates for SERS, herein, we explored a mixed valence state Mo-based metal–organic framework (Mo-MOF) devoid of any embedded noble metal nanoparticles or other enhancing cofactors as a SERS substrate. The Mo-MOF is SERS-activated by irradiation with UV light, which led to a mixed valence state system with an enhancement factor of 1.33 × 10 5 for crystal violet. Our work presents a new approach for the design of non-noble-metal SERS-active substrate materials and extends the applications of MOF materials.